DETEKSI BEGOMOVIRUS PADA TANAMAN CABAI DI MAGELANG INDONESIA - Fariha Wilisiani (Program Studi Agroteknologi INSTIPER, 2019)
Begomovirus is one of the emerging viruses that cause serious disease on chlli plantation worldwide, including Indonesia. Chilli as the important commodity in Indonesia is reported widely infected by begomovirus. Molecular analysis on begomovirus-infecting chilli is important for the disease management of this virus. The purpose of this research is to detect the begomovirus-infecting melon in Magelang, Central Java, as one of the central chilli production in Indonesia. This research was conducted through several phases, which are: yellow and curly leaves collection on the field, virus DNA isolation, and begomovirus detection using universal primer of of this virus. The result of field studies which were conducted in Muntilan, Magelang found some chilli plant with symptom of begomovirus infection. The detection of begomovirus by PCR showed that chilli with yellowing and leaf curl symptoms is positively infected by begomovirus. This study is the report of naturally infection of begomovirus on chilli with yellowing and leaf curl symptoms at Magelang, Central Java, Indonesia. Keyword : chilli, begomovirus, Indonesia